Architectural typological study of coral stone mosques of Maldives / Mohamed Mauroof Jameel - Jameel, Mohamed Mauroof (2012)
Coral stone mosques of Maldives are ancient mosques assembled using finely shaped interlocking 'porite' coral stone from the reef, that have architectural features with coral carvings and detailed lacquer work. These mosques are among the earliest surviving buildings in the country where its cultural heritage is vanishing fast due to rapid changes and development. Little is known about these mosques, and the purpose of this research is to identify the surviving mosques, their state of condition, the influences in their evolution, and to establish a typology in terms of architectural features. The research uses qualitative research methods with multiple surveys and analysis and firstly identifies the surviving mosques and the state of their condition. The research finds that the Maldives government has 203 heritage sites in an unofficial list out of which 46 sites have 51 ancient mosques. The research also finds that 40 out of the 51 ancient mosques survive in different states of condition and 18 of them are confirmed as mosque made from coral stone.